A Phase 1 Dose-Escalation Study of PF-06671008, a Bispecific T-Cell-Engaging Therapy Targeting P-Cadherin in Patients With Advanced Solid Tumors - Harding, James J.; Garrido-Laguna, Ignacio; Chen, Xiaoying; Basu, Cynthia; Dowlati, Afshin; Forgie, Alison; Hooper, Andrea T.; Kamperschroer, Cris; Max, Steven I.; Moreau, Allison; Shannon, Megan; Wong, Gilbert Y.; et al. (Frontiers in Immunology, 2022)
P-cadherin is a cell-cell adhesion molecule that is overexpressed in several solid tumors. PF-06671008 is a T-cell–redirecting bispecific antibody that engages both P-cadherin on tumors and CD3ε on T cells and induces antitumor activity in preclinical models. We conducted a phase 1, open-label, first-in-human, dose-escalation study to characterize the safety and tolerability of PF-06671008, towards determining the recommended phase 2 dose. Adult patients with treatment-refractory solid tumors received PF-06671008 (1.5–400ng/kg) as a weekly intravenous (IV) infusion on a 21-day/3-week cycle. Parallel cohorts evaluated dosing via subcutaneous injection (SC) or an IV-prime dose. Of the 27 patients enrolled in the study, 24 received PF-06671008 IV in escalating doses, two received SC, and one IV-prime. A dose-limiting toxicity of cytokine release syndrome (CRS) occurred in the 400-ng/kg IV group, prompting evaluation of SC and IV-prime schedules. In all, 25/27 patients who received PF-06671008 reported at least one treatment-related adverse event (TRAE); the most common were CRS (21/27), decreased lymphocyte count (9/27), and hypophosphatemia (8/27). Seven patients permanently discontinued treatment due to AEs and no treatment-related deaths occurred. Cytokine peak concentrations and CRS grade appeared to positively correlate with Cmax. Although the study was terminated due to limited antitumor activity, it provides important insights into understanding and managing immune-related AEs resulting from this class of molecules. ClinicalTrials.gov: NCT02659631